A method for preparing silicon-copper alloy by using organic silicon synthesis waste catalyst
Patent Information
- Application Number
- CN202511802213.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-02
AI Technical Summary
这种方法耗费的酸较多,如果要制备硅铜合金需要进一步将硅铜混合后熔融
[0016]本申请的技术效果在于:本申请先将废触体破碎氧化,废触体中的碳首先被除去,其它主要杂质Fe和Al以金属氧化物的形式存在于废触体氧化物中。在熔融电解过程中,Fe3+/Al3+与熔融盐反应形成的络离子溶解度极低,且需要严苛的电位条件,难以在阴极沉积。如此,制备出的硅铜合金纯度较高,所需能耗较低。
Smart Images

Figure CN121428613B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of silicon-copper alloy preparation, and more particularly to a method for preparing silicon-copper alloy using organosilicon synthetic waste catalyst. Background Technology
[0002] In organosilicon synthesis, copper-silicon alloys are commonly used as catalysts. However, during the catalytic reaction, copper and silicon react at high temperatures to form intermetallic compounds with definite stoichiometric ratios, such as Cu3Si and Cu5Si, rather than simple alloy mixtures. These intermetallic compounds have dense crystal structures and lack layered active interfaces, making them unable to reactivate the silicon surface or transfer free radicals. Simultaneously, carbon from chloromethane cracking deposits on the catalyst surface, forming an amorphous carbon layer that further isolates the catalyst from the reactants. Therefore, after a period of time, the catalyst becomes deactivated and becomes a waste catalyst.
[0003] The main components of the waste catalyst are Cu3Si and Cu5Si, and the impurities include elements such as carbon, iron, aluminum, and zinc.
[0004] Currently, the recycling of waste catalysts generally involves smelting or electrodeposition to convert them into silicon-copper alloys or elemental copper and silicon. Smelting involves acid-washing and impurity removal of the waste catalysts before melting them into alloy ingots. Examples include CN 116574932 A and CN118345246 B. However, the main components of waste catalysts are intermetallic compounds, such as Cu3Si, which have strict atomic ratios and ordered crystal structures, and their composition cannot be adjusted. In contrast, alloys, such as silicon-copper alloys, require the random mixing of Cu and Si atoms to form a solid solution, and their composition can be continuously controlled within a certain range, such as a Si content of 5–15 wt%. Directly melting the waste catalysts results in some Cu3Si / Cu5Si only undergoing physical melting, with the atoms maintaining their original ordered arrangement. This prevents the free distribution of Cu and Si, leading to the preparation of silicon-copper alloys containing intermetallic compounds such as Cu3Si, rather than a homogeneous alloy. To disrupt the structure of these intermetallic compounds, higher temperatures are required, and smelting necessitates higher energy consumption.
[0005] Electrodeposition involves preparing a slurry from waste catalysts, followed by acid washing to dissolve the metallic components and obtain silicon. This solution is then electrodeposited to yield elemental copper. Examples include CN 120887425 A and CN 115058586 B. This method consumes a significant amount of acid; further melting and mixing of silicon and copper is necessary to prepare silicon-copper alloys. Additionally, impurities such as Al and Fe can be incorporated into the silicon-copper alloy, reducing its purity.
[0006] In summary, the current method of preparing silicon-copper alloys from waste catalysts has high energy consumption, high acid consumption, and low purity. Summary of the Invention
[0007] In view of this, this application proposes a method for preparing silicon-copper alloy using organosilicon synthetic waste catalysts. The silicon-copper alloy is prepared by molten electrodeposition, which reduces energy consumption and improves the purity of the silicon-copper alloy.
[0008] A method for preparing silicon-copper alloy using organosilicon synthetic waste catalyst includes the following steps: Step 1: Waste catalyst pretreatment: The waste catalyst is crushed and roasted to obtain waste catalyst oxide; Step 2: Electrolyte preparation: NaCl, KCl, NaF, and KF are prepared in a predetermined mass ratio as the electrolyte matrix, and functional additives are added to prepare the electrolyte. Step 3: Mix the waste catalyst oxide and electrolyte and then perform melt electrolysis. Use high and low pulse current to deposit Cu and Si simultaneously to obtain silicon-copper alloy ingots.
[0009] Preferably, the waste catalyst pretreatment includes the following steps: Step 11: Crush and activate the waste catalyst to improve the oxidation reaction rate of the waste catalyst; Step 12: Pre-oxidize at 600℃~650℃ for 1 h to remove carbon deposits on the surface of the waste catalyst; Step 13: Heat to 700℃~750℃ and introduce oxygen-enriched air to enhance the diffusion oxidation of Si.
[0010] Preferably, the waste catalyst pretreatment further includes: Step 14: Remove iron from the calcined waste catalyst oxides using magnetic separation.
[0011] Preferably, the mass ratio of NaCl, KCl, NaF, and KF is 5:3:1:1.
[0012] Preferably, the functional additive includes CaF2, wherein the CaF2 accounts for 5% of the total mass of the electrolyte. Preferably, the functional additive further includes Li2CO3, which accounts for 1% of the total mass of the electrolyte.
[0013] Preferably, the functional additive further includes LiF, which accounts for 6% of the total mass of the electrolyte.
[0014] Preferably, during melt electrolysis, a 1000 A / m pulse is used at a velocity of 10–15 ms. 2 High-current pulses, and 500 A / m pulses lasting 85–90 ms. 2 The low-current pulse, high-current pulse and low-current pulse alternate.
[0015] Preferably, the method for preparing silicon-copper alloys using organosilicon synthetic waste catalysts further includes: Step 4: Vacuum remelting the silicon-copper alloy ingot to improve the properties of the silicon-copper alloy.
[0016] The technical advantage of this application lies in the following: First, the waste catalyst is crushed and oxidized, thus removing carbon from the waste catalyst. Other major impurities, Fe and Al, exist in the waste catalyst oxides in the form of metal oxides. During the molten electrolysis process, Fe... 3 + / Al 3+ The complex ions formed by the reaction with molten salt have extremely low solubility and require stringent potential conditions, making them difficult to deposit on the cathode. Thus, the resulting silicon-copper alloy has high purity and requires less energy. Attached Figure Description
[0017] Figure 1 This is a process flow diagram of the method for preparing silicon-copper alloy using organosilicon synthetic waste catalyst according to this application. Detailed Implementation
[0018] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0019] Please refer to Figure 1 A method for preparing silicon-copper alloy using organosilicon synthetic waste catalyst includes the following steps: Step 1: Waste catalyst pretreatment: The waste catalyst is crushed and roasted to obtain waste catalyst oxide; Step 2: Electrolyte preparation: NaCl, KCl, NaF, and KF are prepared in a predetermined mass ratio as the electrolyte matrix, and functional additives are added to prepare the electrolyte. Step 3: Mix the waste catalyst oxide and electrolyte and then perform melt electrolysis. Use high and low pulse current to deposit Cu and Si simultaneously to obtain silicon-copper alloy ingots.
[0020] This application utilizes a high-temperature molten electrolyte to convert copper oxide and silicon dioxide in organosilicon waste catalyst into ionic states, and then directly prepares silicon-copper alloys by directional reduction deposition at the cathode under the action of an electric field.
[0021] By crushing and roasting the waste catalyst, the carbon and Cu3Si, Cu5Si, etc., in the waste catalyst are transformed into corresponding oxides. Carbon dioxide is released as a gas, and carbon impurities are removed first. At the same time, the crushed waste catalyst has a smaller particle size and is easier to melt.
[0022] After the waste catalyst oxide melts, Cu 2+ and Si 4+ It is reduced to an element under the action of molten electrolyte.
[0023] Chloride-based electrolytes have lower raw material costs, and the volatile gases from chlorides are easier to handle. Furthermore, chloride electrolytes have lower melting points, reducing energy consumption. However, the extremely low solubility of SiO2 in chlorides leads to very low silicon reduction efficiency, making them unsuitable for industrial production. Conversely, while fluoride-based electrolytes can be used for the melt electrolysis of waste catalysts, fluorides themselves are expensive, and their higher melting points result in higher energy consumption. This application, through repeated experiments, established a composite electrolyte system based on NaCl-KCl-NaF-KF. Chlorides provide a low-cost, low-melting-point base, while fluorides enhance silicon dissolution. Under the action of this composite electrolyte, silicon and copper form SiF6. 2- CuCl3 - Complex ions. Functional additives are used to improve the performance of composite electrolytes.
[0024] The main impurities in the calcined waste catalyst oxide are iron oxide and aluminum oxide. In the molten electrolyte system of this application, most of the iron oxide and aluminum oxide are undissolved and suspended in the molten salt as micron-sized particles. After electrolysis, they are discharged with the electrolyte residue and removed by filtration or centrifugation. Some are deposited at the bottom of the molten electrolyte and can be removed periodically. A small portion of the iron oxide reacts with Cl in the molten salt. - FeCl4 is formed - The complex ion has extremely low solubility, <0.5 wt%. A small portion of alumina reacts with F in the molten salt. - Formation of AlF6 3- The complex ion has very low solubility, <0.3 wt%. During cathode reduction, Fe... 3+ / Al 3+ The reduction potential is much lower than that of Cu 2+ and Si 4+ It is difficult to deposit on the cathode. As a result, the prepared silicon-copper alloy has a high purity.
[0025] During molten electrodeposition, this application employs high and low pulsed currents to improve the uniformity of the alloy composition. Specifically, high current density pulsed reduction of Si... 4+ High overpotential overcomes the high activation energy barrier of silicon reduction while suppressing copper concentration polarization, enabling silicon deposition; low current density pulse reduction of Cu 2+ At low overpotentials, copper preferentially deposits due to its high exchange current density. Thus, the current density, by controlling the overpotential, can be used to deposit Si. 4+ and Cu 2+ The reduction is selectively controlled, and a uniform distribution of Cu and Si is achieved by adjusting the pulse time and alternating between high and low pulse currents.
[0026] In a preferred embodiment, the waste catalyst pretreatment includes the following steps: Step 11: Crush and activate the waste catalyst to improve the oxidation reaction rate of the waste catalyst; Step 12: Pre-oxidize at 600℃~650℃ for 1 h to remove carbon deposits on the surface of the waste catalyst; Step 13: Heat to 700℃~750℃ and introduce oxygen-enriched air to enhance the diffusion oxidation of Si.
[0027] The intermetallic compounds in waste catalysts have stable crystal lattices, and direct calcination easily leaves behind undecomposed intermetallic compound particles, making subsequent dissolution difficult. Mechanical grinding of the waste catalysts distorts the crystal lattice, reduces the stability of the intermetallic compounds, and makes them more susceptible to oxidation. Simultaneously, the increased specific surface area of the waste catalysts enhances their oxidation rate, leading to more complete oxidation.
[0028] Because silicon is relatively stable, conventional oxidation processes result in a slow oxidation rate. This means that some silicon may exist in elemental form within the waste catalyst, preventing its enrichment at the cathode during subsequent molten electrolysis and leading to a reduced silicon yield. This application employs a two-stage oxidation process. First, pre-oxidation is performed at 600℃–650℃ for 1 hour to remove carbon deposits from the waste catalyst surface. This reduces impurities in the subsequent silicon-copper alloy and allows for more thorough exposure of the waste catalyst surface. Then, the temperature is increased further, and oxygen-enriched air is introduced to enhance and more completely oxidize the silicon.
[0029] In a preferred embodiment, the waste catalyst pretreatment further includes: Step 14: Remove iron from the calcined waste catalyst oxide using magnetic separation. This mechanical method removes most of the iron impurities, reducing subsequent chloride salt consumption and improving the purity of the silicon-copper alloy.
[0030] In a preferred embodiment, the mass ratio of NaCl, KCl, NaF, and KF is 5:3:1:1.
[0031] This application uses chloride electrolyte as the main component and dopes it with fluoride electrolyte to improve the solubility of silicon and lower the melting point of the molten electrolyte, thereby reducing energy consumption; it can also reduce the cost of the electrolyte itself. Considering the solubility of various oxides in the waste catalyst in molten electrolytes with different proportions, the mass ratio of NaCl, KCl, NaF, and KF is 5:3:1:1.
[0032] In a preferred embodiment, the functional additives include CaF2 and Li2CO3, wherein CaF2 accounts for 5% of the total mass of the electrolyte and Li2CO3 accounts for 1% of the total mass of the electrolyte.
[0033] Chlorides and fluorides have significant density differences, making them prone to stratification at high temperatures. This leads to uneven ion concentration distribution and large fluctuations in the cathode alloy composition. CaF2 can increase the viscosity of the molten electrolyte and suppress its density stratification.
[0034] In actual operation, SiF6 2- The reduction potential is lower, leading to preferential reduction of silicon; while Cl - The presence of Cu will reduce 2+ The activity of CO3 is reduced, inhibiting copper deposition and thus forming "high silicon, low copper" alloys or pure silicon phase alloys, deviating from the target composition. By adding Li2CO3, CO3... 2- With F - Competitive complexation reduces SiF6 2- This activity promotes the co-precipitation of silicon and copper.
[0035] In a preferred embodiment, the functional additive further includes LiF, which accounts for 6% of the total mass of the electrolyte. The LiF can lower the eutectic melting point of the composite electrolyte, thereby reducing energy consumption.
[0036] In a preferred embodiment, during the molten electrolysis of this application, a graphite crucible is used as the electrolytic cell, a stainless steel rod is used as the anode, and a graphite rod is used as the cathode. Because the molten electrolyte of this application is highly corrosive, the inner wall of the graphite crucible is provided with an anti-corrosion layer. This anti-corrosion layer is made of a gradient composite material, which consists of SiC and Al2O3, with the proportion of SiC gradually decreasing from the inside to the outside.
[0037] During electrolysis, the temperature of the molten electrolyte is 580℃~620℃, and the cell voltage is 3.5~4.5 V; Electrolysis is performed by alternating high-current pulses and low-current pulses. The high-current pulse density is 1000 A / m. 2 The duration of each high-current pulse is 10–15 ms; the low-current pulse density is 500 A / m. 2 The duration of each high-current pulse is 85–90 ms.
[0038] In a preferred embodiment, the method for preparing silicon-copper alloy using organosilicon synthetic waste catalyst further includes: Step 4: Vacuum remelting of the silicon-copper alloy ingot to improve the properties of the silicon-copper alloy.
[0039] Silicon-copper alloys prepared by melt electrolysis have some defects, such as the presence of gaseous impurities, soluble ionic impurities, and mechanically entrained impurities, or dendritic segregation. These defects can be improved by vacuum remelting. Vacuum remelting is quite common and will not be described in detail in this application. Although the silicon-iron alloy needs to be remelted during vacuum remelting in this application, the energy consumption is still lower compared to the direct melting of waste catalysts or the mixed melting of silicon powder and copper powder. Before vacuum remelting, silicon-copper is already an alloy. Compared to the elemental form, the alloy has a lower melting point and a shorter melting time. At the same time, compared to waste catalysts, the silicon-copper alloy is bonded by physical doping rather than as an intermetallic compound, resulting in a lower melting point and a shorter melting time.
[0040] The main energy consumption of this application is in the molten electrolysis stage. Although the electrolyte needs to be heated to a molten state, the melting point of the electrolyte is much lower than that of the silicon-copper alloy, and the electrolyte can be used continuously to produce the same mass of silicon-copper alloy. Therefore, the energy consumption required by this application is much less than that of the prior art.
[0041] The solution of this application will be described below with reference to specific embodiments.
[0042] Example 1: Take 1000 kg of waste catalyst from organosilicon synthesis (main components are Cu3Si and Cu5Si, containing 5 wt% carbon, 1.2 wt% Fe, and 0.8 wt% Al), crush it to a particle size of 1-3 mm, place it in a muffle furnace and calcine it in an air atmosphere at a heating rate of 5 °C / min, and hold it at 650 °C for 3 h to obtain waste catalyst oxide. Prepare 500 kg of electrolyte by adding 25 kg of CaF2 and 5 kg of Li2CO3 in a mass ratio of NaCl:KCl:NaF:KF = 50:30:10:10, and mixing thoroughly.
[0043] 200 kg of waste catalyst oxide was mixed with 500 kg of electrolyte and added to a graphite electrolytic cell, then heated to 600 °C. This temperature is the melting point of the electrolyte, much lower than the melting point of CuO / SiO2. High and low pulsed currents were then applied, with a high current density of 1000 A / m. 2 15ms duration, low current density 500 A / m 2 A silicon-copper alloy was prepared using a graphite rod as the anode and a stainless steel rod as the cathode, with a duration of 85 ms and a cycle period of 0.1 s. Waste catalyst oxide was continuously added during this process, along with electrolyte replenishment, until the waste catalyst oxide was completely consumed. After electrolysis, the mixture was cooled to room temperature, and the cathode deposit was peeled off to obtain a silicon-copper alloy ingot.
[0044] Comparative Example 1: Traditional smelting method (refer to CN 116574932 A) Take 1000 kg of organosilicon synthesis waste catalyst from the same batch as in Example 1, and test the content of each component to be basically the same. Crush it directly to a particle size of 5 mm, pickle to remove impurities, melt it in an electric arc furnace at 1500℃, hold it for 4 h to destroy the Cu3Si / Cu5Si structure, and directly cast it to obtain an alloy ingot.
[0045] Comparative Example 2: Electrodeposition method (refer to CN 120887425 A) The same batch of organosilicon synthesis waste catalyst, with essentially the same content of each component as in Example 1, was prepared into a slurry. This slurry was then leached for 4 hours with a mixed acid of 20% H₂SO₄ and 5% HCl at a liquid-to-solid ratio of 5:1. The slurry was filtered to obtain Si powder and Cu-containing... 2+ Solution; Cu powder is obtained by electrodeposition of the solution; Si powder and Cu powder are mixed at a ratio of 8:92 and melted and cast at 1200℃ to obtain alloy ingots.
[0046] The energy consumption during the preparation process of Example 1, Comparative Example 1, and Comparative Example 2, as well as the purity and yield of the obtained silicon-copper alloys, were compared, and the results are shown in Table 1.
[0047] Table 1: As shown in Table 1, the energy consumption of Example 1 is reduced by 68% compared to the smelting method and by 56% compared to the electrodeposition method. This demonstrates that the present application significantly reduces the energy consumption for preparing silicon-copper alloys from waste catalysts.
[0048] Example 1: Calcination pretreatment removes carbon impurities, followed by selective deposition via pulsed current during molten electrolysis. This resulted in a 2.2% increase in purity compared to the smelting method and a 1.5% increase compared to the electrodeposition method. This demonstrates that the present application significantly improves the purity of silicon-copper alloys.
[0049] Example 1: Simultaneous deposition avoids the stepwise extraction and mixing / melting losses associated with electrodeposition, such as Si powder filtration losses and Cu powder oxidation losses, resulting in an 18% increase in total yield compared to electrodeposition and a 12% increase compared to smelting. This demonstrates that this application significantly improves the total yield of Cu and Si in waste catalysts.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing silicon-copper alloy using organosilicon synthetic waste catalyst, characterized in that: Includes the following steps: Step 1: Waste catalyst pretreatment: The waste catalyst is crushed and roasted to obtain waste catalyst oxide; Step 2: Electrolyte preparation: NaCl, KCl, NaF, and KF are prepared in a predetermined mass ratio as the electrolyte matrix, and functional additives are added to prepare the electrolyte. Step 3: After mixing the waste catalyst oxide and electrolyte, perform melt electrolysis, and use high and low pulse current to deposit Cu and Si simultaneously to obtain silicon-copper alloy ingots; Waste catalyst pretreatment includes the following steps: Step 11: Crush and activate the waste catalyst to improve the oxidation reaction rate of the waste catalyst; Step 12: Pre-oxidize at 600℃~650℃ for 1 h to remove carbon deposits on the surface of the waste catalyst; Step 13: Heat to 700℃~750℃ and introduce oxygen-enriched air to enhance the diffusion oxidation of Si; Step 14: Remove iron from the calcined waste catalyst oxides using magnetic separation.
2. The method for preparing silicon-copper alloy using organosilicon synthesis waste catalyst as described in claim 1, characterized in that: The mass ratio of NaCl, KCl, NaF, and KF is 5:3:1:
1.
3. The method for preparing silicon-copper alloy using organosilicon synthesis waste catalyst as described in claim 1, characterized in that: The functional additive includes CaF2, which accounts for 5% of the total mass of the electrolyte.
4. The method for preparing silicon-copper alloy using organosilicon synthesis waste catalyst as described in claim 1, characterized in that: The functional additive also includes Li2CO3, which accounts for 1% of the total mass of the electrolyte.
5. The method for preparing silicon-copper alloy using organosilicon synthesis waste catalyst as described in claim 1, characterized in that: The functional additive also includes LiF, which accounts for 6% of the total mass of the electrolyte.
6. The method for preparing silicon-copper alloy using organosilicon synthesis waste catalyst as described in claim 1, characterized in that: During melt electrolysis, a 1000 A / m pulse is used at a speed of 10–15 ms. 2 High-current pulses, and 500 A / m pulses lasting 85–90 ms. 2 The low-current pulse, high-current pulse and low-current pulse alternate.
7. The method for preparing silicon-copper alloy using organosilicon synthesis waste catalyst as described in claim 1, characterized in that: Methods for preparing silicon-copper alloys using organosilicon synthetic waste catalysts also include: Step 4: Vacuum remelting the silicon-copper alloy ingot to improve the properties of the silicon-copper alloy.
Citation Information
Patent Citations
A method for recovering copper and silicon powder from waste organic silicon contacts
CN115058586B
Method for preparing silicon-containing alloy by using organic silicon waste contact
CN116574932A
A method for preparing silicon-copper alloy and high-purity silicon using waste organic silicon contacts
CN118345246B
Method for purifying silicon from organic silicon synthesis waste contact and application in preparation of silicon-based alloy
CN120887425A
Method of electrodepositing silicon
CN101054675A